1992
DOI: 10.1007/bf03348804
|View full text |Cite
|
Sign up to set email alerts
|

Bone histomorphometry in Cushing’s syndrome

Abstract: Bone involvement is a common finding in Cushing's syndrome. The actions of corticosteroids on bone have been studied quite intensively but only a few studies of bone histomorphometry in this syndrome have been published. In this paper we present histomorphometric measurements of bone activity in 7 patients with a postoperative reevaluation in two. The results show irregular alterations on histomorphometric parameters with an increased bone resorption and decreased bone formation rate. After surgery the abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…This finding was interesting because, as aforementioned, GIO in humans generally results in more pronounced changes in the BMD of trabecular bone compared to cortical bone. However, in line with the CRH‐Tg model, several studies have shown significant decreases in cortical thickness with Cushing's syndrome; and a very recent study using high‐resolution quantitative CT showed that patients with Cushing's syndrome exhibited deleterious effects primarily on cortical bone microstructure (lower cortical areas, thicknesses, and vBMD) when compared to age‐ and sex‐matched controls . The decreased trabecular thickness observed in CRH‐Tg mice is also in agreement with several studies that have shown exogenous administration of GC drugs causes trabecular thinning (reviewed in Dalle Carbonare and colleagues).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This finding was interesting because, as aforementioned, GIO in humans generally results in more pronounced changes in the BMD of trabecular bone compared to cortical bone. However, in line with the CRH‐Tg model, several studies have shown significant decreases in cortical thickness with Cushing's syndrome; and a very recent study using high‐resolution quantitative CT showed that patients with Cushing's syndrome exhibited deleterious effects primarily on cortical bone microstructure (lower cortical areas, thicknesses, and vBMD) when compared to age‐ and sex‐matched controls . The decreased trabecular thickness observed in CRH‐Tg mice is also in agreement with several studies that have shown exogenous administration of GC drugs causes trabecular thinning (reviewed in Dalle Carbonare and colleagues).…”
Section: Discussionsupporting
confidence: 83%
“…In line with this, there is a higher incidence of fractures in the femoral neck and vertebrae; compartments that have a higher percentage of trabecular bone . However, cortical bone is also significantly affected by GCs, and a recent study of Cushing's syndrome patients using micro–computed tomography (μCT) for analysis revealed a dominant effect of GCs on cortical bone microstructure . It is therefore important to consider all parameters in parallel when studying the effects of GCs on the skeleton.…”
Section: Introductionmentioning
confidence: 99%
“…GCs exert complex effects on the skeleton, either inhibiting or enhancing, which are dependant on the species under investigation, the developmental stage as well as the concentration and duration of GC exposure [22]. In vitro, a low concentration of GCs induces cells of the osteoblast lineage to differentiate into mature OBs [23][24][25][26][27][28], whereas GCs at high concentrations dramatically decrease OB number and bone formation rate [29][30][31].…”
Section: Cellular Effects Of Gcsmentioning
confidence: 99%
“…Glucocorticoids decrease bone formation and stimulate bone resorption, the latter partly secondary to reduced intestinal calcium absorption (1). In accord, histomorphometric studies in steroid-induced osteopenia have shown decreased bone formation rate and signs of increased bone resorption (2)(3)(4). Bone mineral content (BMC) and density (BMD) are markedly decreased in untreated CS, with significant improvement following treatment (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 97%